Two-scale modelling of reactive powder concrete. Part I: representative volume element and solution of the corresponding boundary value problem = Dwuskalowy model betonu z proszków reaktywnych. Część I: reprezentatywny element objętościowy (RVE) i rozwiązanie zagadnienia brzegowego na RVE - Denisiewicz, Arkadiusz; Kuczma, Mieczysław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is the first part of a series concerned with the modelling of reactive powder concrete by using a numerical homogenization technique. This technique is a multi-scale modelling approach. Specifically, in this paper a two scale modelling concept was applied. A model of reactive powder concrete (RPC) is considered whose behaviour on the macro scale is described on the basis of the phenomena occurring in the microstructure of the material.
Keywords: beton typu RPC; modelowanie wieloskalowe; homogenizacja numeryczna; multiscale modelling; RPC; microscale; computational homogenization; RVE